INTEGRATED APPROACHES, NEW TRENDS AND INNOVATIONS IN MENU DEVELOPMENT FOR THE RESTAURANT INDUSTRY (Development Service Industry Management, 2024)
The article examines modern approaches to menu development in restaurant business establishments, highlighting its pivotal role in shaping an establishment's image, attracting customers, and improving financial performance. The study explores marketing, technological, creative, ecological, and customer-oriented approaches, each contributing to the menu's attractiveness and relevance. The primary functions of a menu are analyzed, including its informational, marketing, managerial, quality control, and customer satisfaction roles. Key trends are discussed, such as the incorporation of local and seasonal ingredients, healthy dining options, innovative cooking techniques, and interactive elements. The article underscores the importance of adapting menus to shifts in demand, evolving gastronomic trends, and changing customer preferences. Emphasis is placed on the role of innovation in enhancing the competitiveness of food service establishments. Current trends influencing menu development are also highlighted, including the rising demand for local and seasonal products, healthier food choices, vegan and vegetarian options, and exotic ingredients. Additionally, the importance of continual menu adaptation to dynamic market needs, customer preferences, and emerging culinary trends is stressed. This adaptability is essential for restaurants to maintain their competitiveness and relevance in the ever-evolving food service industry.
Keywords: restaurant business; menu; trends; innovations; competitiveness